Changes in barley malting quality and mycotoxin contamination associated with warm nights and Fusarium graminearum infection under climate change scenarios - Mauro Martínez; Carolina Manno; Agustín F. Arata; María I. Dinolfo; Eduardo De Gerónimo; Juan Ignacio Poo; Agustín Mosca; Germán González; Sebastián A. Stenglein (European Journal of Plant Pathology, 2026)

The 2020 national seismic hazard model for the United Kingdom - I. Mosca; S. Sargeant; B. Baptie; R. M. W. Musson; T. C. Pharaoh (Bulletin of Earthquake Engineering, 2022)
We present updated seismic hazard maps for the United Kingdom (UK) intended for use with the National Annex for the revised edition of Eurocode 8. The last national maps for the UK were produced by Musson and Sargeant (Eurocode 8 seismic hazard zoning maps for the UK. British Geological Survey Report CR/07/125, United Kingdom, 2007). The updated model uses an up-to-date earthquake catalogue for the British Isles, for which the completeness periods have been reassessed, and a modified source model. The hazard model also incorporates some advances in ground motion modelling since 2007, including host-to-target adjustments for the ground motion models selected in the logic tree. For the first time, the new maps are provided for not only peak ground acceleration (PGA) but also spectral acceleration at 0.2 s (SA 0.2s ) and 1.0 s for 5% damping on rock (time-averaged shear wave velocity for the top 30 m Vs30 ≥ 800 m/s) and four return periods, including 475 and 2475 years. The hazard in most of the UK is generally low and increases slightly in North Wales, the England–Wales border region, and western Scotland. A similar spatial variation is observed for PGA and SA 0.2s but the effects are more pronounced for SA 0.2s . Hazard curves, uniform hazard spectra, and disaggregation analysis are calculated for selected sites. The new hazard maps are compared with the previous 2007 national maps and the 2013 European hazard maps (Woessner et al. in Bull Earthq Eng 13:3553–3596, 2015). There is a slight increase in PGA from the 2007 maps to this work; whereas the hazard in the updated maps is lower than indicated by the European maps.